2022
DOI: 10.18860/dsjpips.v1i3.2061
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Ekonomi Dan Kontrol Diri Terhadap Perilaku Pembelian Impulsif Pada Mahasiswa

Abstract: The COVID-19 pandemic, which was followed by technological developments, caused people to carry out all their activities at home, which was accompanied by an increase in the intensity of internet use. This gives rise to a new phenomenon called impulsive buying behavior. Based on these problems, researchers intend to find out how the picture of impulsive buying behavior is from the side of students who have economic literacy accompanied by self-control. This study aims to test whether there is an influence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
0
0
2
Order By: Relevance
“…Second Hypothesis: FoMO (Fear of Missing Out) (X1) has a positive and significant effect on Religiosity (Z) with a P value of 0.014 or <0.05, so it can be concluded that there is a significant effect of FoMO (Fear of Missing Out) on Religiosity in Palembang City People who Shop at Shopee E-Commerce. The results of this study are in line with research conducted by Siti (Siti Nurjannah, 2023) showing that FoMO (Fear of Missing Out) has a positive and significant effect on Religiosity. Meanwhile, Santoso et al's research shows the results that FoMO (Fear of Missing Out) has no positive and significant effect on Religiosity.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Second Hypothesis: FoMO (Fear of Missing Out) (X1) has a positive and significant effect on Religiosity (Z) with a P value of 0.014 or <0.05, so it can be concluded that there is a significant effect of FoMO (Fear of Missing Out) on Religiosity in Palembang City People who Shop at Shopee E-Commerce. The results of this study are in line with research conducted by Siti (Siti Nurjannah, 2023) showing that FoMO (Fear of Missing Out) has a positive and significant effect on Religiosity. Meanwhile, Santoso et al's research shows the results that FoMO (Fear of Missing Out) has no positive and significant effect on Religiosity.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Semakin dewasa individu, maka kemampuannya dalam melakukan Self -Management juga akan semakin baik. Selaras dengan pendapat (Atunnisa' & Firdiansyah, 2022) yang menyatakan bahwa faktor dari dalam diri yang memiliki peran dalam melakukan Self -Management ialah usia, kemampuan seseorang untuk mengendalikan diri akan semakin baik seiring dengan kian bertambahnya usia seseorang.…”
unclassified
“…Kemudian secara simultan, baik financial education maupun self -management sama-sama memberikan pengaruh terhadap Impulsive buying. Penelitian tersebut juga didukung oleh hasil penelitian dari (Atunnisa' & Firdiansyah, 2022) yang membuktikan tidak adanya pengaruh antara Financial Education terhadap Impulsive buying, sedangkan Self Management memiliki pengaruh terhadap Impulsive buying , dan secara simultan baik financial education maupun Self -Management sama-sama berpengaruh terhadap Impulsive buying.…”
unclassified